FRI0293 Rheumatoid arthritis and spondyloarthropathies in clinical remission have the same rates of flare in pregnancy, more elevated if therapy before conception was a biologic agent. (23rd January 2014) - Giacuzzo, S.; Padovan, M.; Castellino, G.; Capucci, R.; Govoni, M.
Abstract : Background: The activity of the rheumatic diseases can be influenced by pregnancy and puerperium. Improvement of rheumatoid arthritis (RA) and psoriatic arthritis (PA) was described in retrospective studies in about 75% of pregnant patients, whereas in ankylosing spondylitis (AS) there is no relevant change in disease activity. Most of these data come from study in which were enrolled patients with moderate-hight disease activity at pregnancy onset. Objectives: to assess rate of disease flare in patients with RA and spondyloarthropathies (SpA) in clinical remission during and after pregnancy Methods: We included 18 patients with RA (19 pregnancies), 12 with undifferentiated spondyloarthropathies (14 pregnancies), 4 with psoriatic arthritis and 2 with ankylosing spondylitis (AS) in clinical remission (DAS28-PCR-3v <2.6; BASDAI <4, no extra-articular manifestations) at last visit before pregnancy. Twelve patients were exposed to anti-TNF agents (5 with RA and 7 with SpA) wich were stopped when pregnancy started and 1 patient with RA had completed the last cycle with Rituximab 3 months beforeconception. Clinical examination was performed monthly during pregnancy and 12 weeks post-delivery. Assessment of RA and SpA with peripheral arthritis was performed by DAS28-CRP with 3 variables (DAS28-CRP-3v) and assessment of AS by the BASDAI. Disease flare was defined as increase in DAS28>1.2, BASDAI >4 or new/worsened extra-articular manifestations requiring therapy. Results: Disease relapses in RA and SpA were observed respectively in 26% and 15% in first trimester, 42% and 15% in second trimester, 21% and 30% in third trimester, 61% and 55% in puerperium. Clinical remission was persistently maintained during gestation in 53% of RA patients and 50% of SpA patients. Although we found a trend of high rate of relapses during the second trimester in patients with RA it was not statistically significant. It is worth noting that the highest rates of flares occurred in patients previously exposed to biotechnology drugs, regardless of the underlying disease (100% vs 50%; p 0.0018). Conclusions: Disease relapse occurred with similar rates in RA and SpA patients during pregnancy and puerperium. The rates of relapse were higher in patient previously treated with biologic agents, probably because of greater severity of underlying disease. Data coming from this preliminary analysis demonstrated that rheumatic diseases in clinical remission reached after biologic treatment may be at risk of relapse when these drugs are withdrawn in early pregnancy. Disclosure of Interest: None Declared